PENDAMPINGAN LITERASI SAINS DALAM PEMBELAJARAN DI SDN JELAMBAR BARU 01 PAGI [SCIENCE LITERACY ASSISTANCE IN LEARNING AT SDN JELAMBAR BARU 01 PAGI] - Harlinda Syofyan; Ratnawati Susanto; Yeni Duriana; Vebryanti -; Melinda Tesaniloka (Universitas Pelita Harapan, 2019)
Literacy is not just the ability to read and write but adds knowledge, skills, and abilities that can make a person have ability to think critically, solve problems in various contexts, communicate effectively, develop potential and actively participate in social life. Community Partnership Program Activities in 2019 will be held at SDN Jelambar Baru 01 Pagi West Jakarta. This activity is carried out based on realizing a generation that can have broad insights into literacy activities that will guide them to be able to think critically. For this reason, teachers are trained to stimulate their students with problems and examples that are contextual with the subject matter so that teachers are able to explore their students' knowledge in teaching and learning activities so that partner schools can achieve performance targets both in aspects of learning, so mentoring Science Literacy to teachers in increasing the ability and understanding of their students. The method used is (active participatory methods in mentoring both in the socialization, discussion, and equalization of perceptions between the PKM team and teachers in partner schools. The results of this PKM from observation and evaluation there is a significant increase in literacy mastery for illustrated teachers from the lesson plans that they arrange to be implemented in learning.